Educational Quality Standards and Their Uninterrupted Monitoring as a Condition for Ensuring Sustainable Development of Education . - Olena, Kuzmak (National Interest, 2022)
In the conditions of globalization and sustainable development there is an acute need to improve and restructure the educational sector of Ukraine. The key issue is the development of internal and external quality assurance systems for higher education, improving the quality of educational services, forming an effective management system that takes into account the specifics of ensuring, taking into account and satisfying interests between stakeholders and universities. The process of measuring and improving the quality of educational services is researched. An algorithm for continuous measurement of the quality of provided educational services by the university is proposed. Based on the analysis of indicators of quality of provided educational services and profitability of relationships with students, we proposed a matrix of relationships between universities and students, which allows the university to choose a customer-oriented strategy of behavior in the market of educational services.